2003
DOI: 10.1007/s00464-002-9161-7
|View full text |Cite
|
Sign up to set email alerts
|

The influence of adhesion prophylactic substances and taurolidine/heparin on local recurrence and intraperitoneal tumor growth after laparoscopic-assisted bowel resection of colon carcinoma in a rat model

Abstract: Taurolidine/heparin led to a significant reduction of intraperitoneal tumor growth after intraperitoneal application, whereas local tumor recurrence was not significantly influenced. This might be due to the number of injected tumor cells in this cell suspension model. Interceed and Intergel did not reduce intraperitoneal tumor growth. Furthermore, adhesion formation was not reduced by any of the substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 51 publications
1
13
0
1
Order By: Relevance
“…These results confirm previous studies where the antineoplastic effect of taurolidine has been proven in vitro in melanoma, glioblastoma [24] , ovarian cancer, colon cancer, melanoma and lung cancer cell lines [16] and also in vivo in colon cancer [25] and pancreatic cancer animal models [26,27] .…”
Section: Discussionsupporting
confidence: 81%
“…These results confirm previous studies where the antineoplastic effect of taurolidine has been proven in vitro in melanoma, glioblastoma [24] , ovarian cancer, colon cancer, melanoma and lung cancer cell lines [16] and also in vivo in colon cancer [25] and pancreatic cancer animal models [26,27] .…”
Section: Discussionsupporting
confidence: 81%
“…Many experimental and clinical studies have revealed that taurolidine has significant antiadherent activity on pathogen microorganisms, and although the data are conflicting, possibly decreases postoperative peritoneal adhesion formations. [17][18][19]27 Opitz et al 17 showed in an experimental study that the use of heparin and taurolidine led to a significant reduction of intraperitoneal tumor growth, however, did not decrease the severity of adhesions. In contrast, a recent study comparing the effectiveness of Seprafilm \ and taurolidine revealed similar results when the products were used for the purpose of preventing mesh-induced adhesions.…”
Section: Discussionmentioning
confidence: 97%
“…16 Finally, experimental studies have demonstrated that the product may be used as an antiadhesive, probably as a consequence of its antimicrobial and antiproliferative effects. [17][18][19] In addition, advantages, such as cost effectiveness and liquid form of the product, may lead the acceptance of its use in open and laparoscopic surgery.…”
mentioning
confidence: 99%
“…However, since our experiment was designed with a comparatively high number of CC531 tumor cells, complete prevention of intraperitoneal tumor growth was not possible. Other work groups have used significantly fewer tumor cells [15,18]. Our aim was to rapidly achieve a larger tumor mass in order to better demonstrate the effect of taurolidine.…”
Section: Discussionmentioning
confidence: 99%